Estimating the effects of non-discriminatory trade policies within structural gravity models - Benedikt Heid; Mario Larch; Yoto V. Yotov (Canadian Journal of Economics/Revue canadienne d'économique, 2021)
We propose a simple method to identify the effects of unilateral and non-discriminatory trade policies on bilateral trade within a theoretically consistent empirical gravity model. Specifically, we argue that structural gravity estimations should be performed with data that include not only international trade flows but also intra-national trade flows. The use of intra-national sales allows identification of the effects of non-discriminatory trade policies such as most favoured nation tariffs, even in the presence of exporter and importer fixed effects. A byproduct of our approach is that it can be used to recover estimates of the trade elasticity, a key parameter for quantitative trade models. We demonstrate the effectiveness of our techniques in the case of most favoured nation tariffs and “time to export” as representative non-discriminatory determinants of trade on the importer and on the exporter side, respectively. Our methods can be extended to quantify the impact on trade of any country-specific characteristics as well as any non-trade policies.
Keywords: 330